High-temperature-resistant, high-humidity-resistant and oil-resistant food fresh-keeping composite nano film and preparation method thereof
Through the multi-layer structure of food preservation composite nano film, combined with the combination technology of polylactic acid, konjac glue and chitosan, the problem of degradation of mechanical properties of bio-based packaging materials in high temperature and high humidity environments is solved, and efficient food preservation and Antibacterial effect.
Patent Information
- Application Number
- CN202411432166.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The mechanical properties of existing bio-based food packaging materials are prone to decline in high temperature or high humidity environments, resulting in easy destruction of packaging materials and affecting the food preservation effect.
The multi-layer structure of high-temperature, high humidity, oil-resistant food fresh-preserving composite nano film, including polylactic fiber membrane layer, konjac gum antibacterial layer and modified konjac gum chitosan composite antibacterial layer, was prepared by electrospinning and electrostatic spraying technology. A combination of polylactic acid, konjac gum and chitosan is used to form a film with excellent high temperature and high humidity resistance and antibacterial effect.
At 45℃ and 95% humidity for 24 hours, the tensile strength loss rate is less than 7%, and the elongation loss rate of break is less than 11%. At the same time, it has a 99.9% antibacterial rate for E. coli, which significantly improves the mechanics of food packaging materials Performance and freshness.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multilayer structure new materials, relates to food packaging materials, and specifically relates to a high temperature, high humidity and oil resistant food preservation composite nano film and a preparation method thereof. Background Art
[0002] Preserved food packaging materials are often used for food storage, transportation and preservation. Their performance often plays a decisive role in the quality of food and is closely related to people's dietary health. Traditional metal and glass packaging materials are completely airtight and are good packaging materials, but they are not suitable for the preservation of fresh products such as fruits and vegetables that have respiratory functions. Fresh fruits and vegetables and cold meat have physiological activities such as respiratory functions, so storage and preservation are areas that need to be solved urgently, and there is a strong demand in the food market. Therefore, the development of other packaging materials has always been one of the key research directions in this field.
[0003] Bio-based packaging materials have been a hot topic in recent years. They have the advantages of easy availability of raw materials, health and environmental protection, and easy preparation. [1] However, when existing bio-based materials are used to prepare food packaging products, they face the problem that their mechanical properties are prone to a significant decrease in high temperature or high humidity environments, resulting in low application value of packaging products prepared with bio-based materials.
[0004] There have been many studies on the preparation of high-temperature resistant products using polymer materials, such as a large number of products that are actually used in the field of building materials or medical fields. In terms of food packaging, researchers have also conducted relevant research. For example, CN115490965B announced a food packaging film that can be heated at high temperature and its production process. The packaging film uses a variety of polymer materials as raw materials and adds heat-resistant agents to obtain good heat resistance. However, there are many ingredients in this patent, and its heat resistance is to measure the highest temperature at which no relevant ingredients seep out, and the effect of high temperature on mechanical strength is not examined. In reality, the temperature increase caused by weather changes, cross-border transportation or other reasons can easily affect the mechanical properties of packaging materials, making the packaging materials easily damaged and causing food to be exposed and deteriorate. Therefore, it is very necessary to study packaging films whose mechanical properties are less affected by environmental factors such as temperature and humidity during use.
[0005] At present, as far as the inventor knows, in the field of food, there are relatively few studies on how to make the mechanical strength of packaging films less affected by environmental factors. The few studies that have been conducted are limited to a few packaging materials, such as Tulan Ying. [2] et al. developed an edible protein film that is resistant to high temperature and humidity, but the resulting product has low mechanical strength and limited application scenarios.
[0006] Therefore, how to develop packaging materials with other substrates as raw materials whose mechanical strength is less affected under high temperature, high humidity and other environments is urgently needed in this field.
[0007] [1] Zhu Yingao, Chen Qian, Kong Baohua, et al. Research progress on antibacterial properties of bio-based nanocomposite food packaging materials[J]. Journal of Chinese Institute of Food Science and Technology, 2024, 24(01): 466-474.
[0008] [2]Tu Lanying, Zhao Qiwen, Yue Xiangguo. Development of edible protein film resistant to high temperature and humidity[J]. Hubei Agricultural Sciences, 2014, 53(22): 5497-5499. Summary of the invention
[0009] In view of the defects of the prior art, the purpose of the present invention is to provide a new multilayer structure material and a preparation method thereof, which is used as a food packaging film and can maintain good mechanical properties and has good antibacterial effect in high temperature, high humidity or oil immersion environment.
[0010] In order to achieve the above object, the present invention provides the following technical solutions:
[0011] A method for preparing a high temperature, high humidity and oil-resistant food preservative composite nanofilm, wherein the high temperature, high humidity and oil-resistant food preservative composite nanofilm is a multilayer structure, comprising a polylactic acid fiber film layer, a konjac gum antibacterial layer, and a modified konjac gum chitosan composite antibacterial layer; the preparation method comprises the following steps:
[0012] (1) electrospinning a polylactic acid solution to form an electrospun fiber membrane as a first polylactic acid fiber membrane layer;
[0013] (2) electrostatically spraying a konjac glucomannan solution containing an antibacterial substance A on one side of the electrospun membrane obtained in step (1) to form a konjac glucomannan antibacterial layer;
[0014] (3) Based on the product obtained in step (2), electrospinning is performed using a polylactic acid solution on the side where the electrostatic spraying is completed to form a second polylactic acid fiber film layer;
[0015] (4) electrostatically spraying the outer side of the obtained product of step (3) with a composite solution of modified konjac gum and chitosan containing an antibiotic B to form a composite antibacterial layer of modified konjac gum and chitosan;
[0016] The modified konjac gum is obtained by acid hydrolyzing with citric acid, precipitating with ethanol, and freeze-drying the precipitate.
[0017] In the composite solution of modified konjac gum and chitosan, the weight ratio of modified konjac gum to chitosan is 3 to 5:1;
[0018] The antibacterial substance A is an aqueous extract of Zanthoxylum bungeanum leaves; the antibacterial substance B is an aqueous extract of a mixture of dark red roses and grape seeds, and the weight ratio of dark red roses to grape seeds is 2:1;
[0019] When electrostatic spinning is performed in step (1) and step (3), the weight ratio of the polylactic acid used is 0.8-1.2:0.8-1.2; when electrostatic spraying is performed in step (2), the weight of the konjac glucomannan used is 0.2-0.4 times the weight of the polylactic acid used in step (1); when electrostatic spraying is performed in step (4), the total weight of the modified konjac glucomannan and chitosan used is 0.2-0.4 times the weight of the polylactic acid used in step (1).
[0020] Preferably, the modified konjac glucomannan is prepared by the following method: adding konjac glucomannan to a citric acid aqueous solution so that the weight fraction of konjac glucomannan is 10%, and the weight molar ratio of konjac glucomannan to citric acid is 10g:1.6mmol; after stirring evenly, reacting at 80°C for 2 hours; then adding 2 times the volume of an ethanol aqueous solution with a volume fraction of 95%, stirring evenly, standing to produce a precipitate, and vacuum freeze-drying the precipitate to obtain the modified konjac glucomannan.
[0021] Preferably, the solvent in the polylactic acid solution is dichloromethane, and the weight fraction of polylactic acid in the polylactic acid solution is 6%.
[0022] Preferably, the solvent of the konjac gum solution in step (2) is a mixed solvent of ethanol and acetic acid in a volume ratio of 5:4, and the weight fraction of konjac gum in the konjac gum solution is 1%.
[0023] Preferably, in step (4), the solvent in the modified konjac gum and chitosan composite solution is a mixed solvent of ethanol and acetic acid mixed in a volume ratio of 1:1, the weight fraction of the sum of the modified konjac gum and chitosan is 1%, and the weight ratio of the modified konjac gum and chitosan is 4:1.
[0024] Preferably, when electrostatic spinning is performed in step (1) and step (3), the weight ratio of the polylactic acid used is 1:1; when electrostatic spraying is performed in step (2), the weight of the konjac glucomannan used is 0.3 times the weight of the polylactic acid used in step (1); when electrostatic spraying is performed in step (4), the weight of the konjac glucomannan used on each side is 0.3 times the weight of the polylactic acid used in step (1).
[0025] Preferably, when electrospinning is performed in step (1) and step (3), the voltage is 15 kV, the temperature is 25°C, the receiving distance is 15 cm, and the propulsion speed is 35 μL / min; when electrostatic spraying is performed in step (2) and step (4), the voltage is 20 kV, the temperature is 25°C, the receiving distance is 15 cm, and the propulsion speed is 50 μL / min.
[0026] Preferably, the preparation method of the water extract of Zanthoxylum bungeanum leaves is as follows: take the Zanthoxylum bungeanum leaves, cut them into pieces, add 10 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 10 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; and perform rotary evaporation drying on the combined filtrate to obtain the obtained product. The preparation method of the water extract of the mixture of dark red rose and grape seed is as follows: take the dark red rose according to the weight ratio, cut it into pieces, mix it with grape seeds, add 15 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 15 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; and perform rotary evaporation drying on the combined filtrate to obtain the obtained product.
[0027] Preferably, the weight of the antibacterial substance A is 2% of the weight of the konjac gum; the weight of the antibacterial substance B is 2% of the total weight of the modified konjac gum and chitosan.
[0028] The present invention also provides a high temperature, high humidity and oil resistant food preservation composite nano film prepared by the above preparation method.
[0029] Beneficial effects of the present invention
[0030] The food preservation composite nanofilm obtained by the present invention has excellent high temperature and high humidity resistance. At 45°C and 95% humidity for 24 hours, the tensile strength loss rate is less than 7%, and the elongation at break loss rate is less than 11%. At the same time, the food preservation composite nanofilm obtained by the present invention also has an excellent antibacterial rate. 4 At a bacterial concentration of 1.5 cfu / mL, the inhibition rate against Escherichia coli can reach 99.9%. DETAILED DESCRIPTION
[0031] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel in this field based on the above invention content still fall within the scope of protection of the present invention.
[0032] The raw materials used in the following examples and comparative examples are as follows:
[0033] Polylactic acid: Beijing Yongkang Leye Technology Development Co., Ltd., product number PLA86;
[0034] Konjac gum: Anhui Qianshun Biotechnology Co., Ltd., product number KJ-30;
[0035] Chitosan: Nanjing Deju Biotechnology Co., Ltd., product number 3224232;
[0036] Gelatin: Jiangsu Guangrui Biotechnology Co., Ltd., product number 01;
[0037] Modified konjac gum: adding konjac gum to a citric acid aqueous solution so that the weight fraction of konjac gum is 10%, and the weight molar ratio of konjac gum to citric acid is 10g:1.6mmol; after stirring evenly, reacting at 80°C for 2 hours; then adding 2 times the volume of 95% ethanol aqueous solution, stirring evenly and standing to produce precipitation, and vacuum freeze-drying the precipitation to obtain;
[0038] Water extract of Zanthoxylum bungeanum leaves: chop the Zanthoxylum bungeanum leaves into small pieces, add 10 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 10 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; dry the combined filtrate by rotary evaporation to obtain;
[0039] Dark red rose water extract: cut dark red rose into pieces, add 10 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 10 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; dry the combined filtrate by rotary evaporation to obtain;
[0040] Grape seed water extract: take grape seeds, add 10 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 10 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; dry the combined filtrate by rotary evaporation to obtain;
[0041] Aqueous extract of a mixture of dark red roses and grape seeds: cut the dark red roses into pieces and mix them with grape seeds in a weight ratio of 2:1, add 15 times the weight of water, boil and extract for 2 hours, take the filtrate to obtain a primary filtrate; add 15 times the weight of water to the filter residue, boil and extract for 2 hours, take the filtrate to obtain a secondary filtrate, combine the primary filtrate and the secondary filtrate to obtain a combined filtrate; and perform rotary evaporation drying on the combined filtrate to obtain the product.
[0042] Example 1
[0043] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane as the first polylactic acid fiber membrane layer; during electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0044] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1) to form a konjac glucomannan antibacterial layer; during the electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 30% of the weight of the polylactic acid used in step (1);
[0045] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1) to form a second polylactic acid fiber film layer, and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0046] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seed, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 4:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the water extract of the mixture of dark red rose and grape seed is 2% of the total weight of modified konjac gum and chitosan; spraying the outer sides of both sides with the electrostatic spray solution obtained in this step in step (3) The liquid is electrostatically sprayed to form a modified konjac gum chitosan composite antibacterial layer; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when this step electrostatically sprays the outer sides of step (3) on both sides, the weight of the sum of the modified konjac gum and chitosan used on each side is 30% of the weight of the polylactic acid used in step (1); after completing the spraying, being placed in a special container and the residual organic solvent in the obtained membrane material is volatilized by vacuumizing to obtain a composite nano-membrane.
[0047] Example 2
[0048] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane as the first polylactic acid fiber membrane layer; during electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0049] (2) collecting the electrospun membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospun membrane obtained in step (1) to form a konjac glucomannan antibacterial layer; during the electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 40% of the weight of the polylactic acid used in step (1);
[0050] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1) to form a second polylactic acid fiber film layer, and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 2:3;
[0051] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seed, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 5:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the water extract of the mixture of dark red rose and grape seed is 2% of the total weight of modified konjac gum and chitosan; spraying the outer sides of both sides with the electrostatic spray solution obtained in this step in step (3) The liquid is electrostatically sprayed to form a modified konjac gum chitosan composite antibacterial layer; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when this step electrostatically sprays the outer sides of step (3) on both sides, the weight of the sum of the modified konjac gum and chitosan used on each side is 40% of the weight of the polylactic acid used in step (1); after completing the spraying, being placed in a special container and the residual organic solvent in the obtained membrane material is volatilized by vacuumizing to obtain a composite nano-membrane.
[0052] Example 3
[0053] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane as the first polylactic acid fiber membrane layer; during electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0054] (2) collecting the electrospun membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospun membrane obtained in step (1) to form a konjac glucomannan antibacterial layer; during the electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 20% of the weight of the polylactic acid used in step (1);
[0055] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1) to form a second polylactic acid fiber film layer, and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 3:2;
[0056] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seed, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 3:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the water extract of the mixture of dark red rose and grape seed is 2% of the total weight of modified konjac gum and chitosan; spraying the outer sides of both sides with the electrostatic spray solution obtained in this step in step (3) The liquid is electrostatically sprayed to form a modified konjac gum chitosan composite antibacterial layer; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when this step electrostatically sprays the outer sides of step (3) on both sides, the weight of the sum of the modified konjac gum and chitosan used on each side is 20% of the weight of the polylactic acid used in step (1); after completing the spraying, being placed in a special container and the residual organic solvent in the obtained membrane material is volatilized by vacuumizing to obtain a composite nano-membrane.
[0057] Comparative Example 1
[0058] Compared with Example 1, the main difference is that the modified konjac gum in step (4) is replaced by konjac gum, and the specific scheme is as follows:
[0059] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during the electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0060] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1); during electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 30% of the weight of the polylactic acid used in step (1);
[0061] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1), and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0062] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seeds, konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of konjac gum and chitosan is 4:1, the weight fraction of the sum of konjac gum and chitosan is 1%, and the weight of the water extract of the mixture of dark red rose and grape seeds is 2% of the total weight of modified konjac gum and chitosan; electrostatic spraying is performed on the outer sides of both sides of step (3) using the electrostatic spray solution obtained in this step; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when electrostatic spraying is performed on the outer sides of both sides of step (3) in this step, the weight of the konjac gum used on each side is 30% of the weight of the polylactic acid used in step (1); after spraying is completed, placing in a special container and evacuating the residual organic solvent in the obtained membrane material to obtain a composite nano-membrane.
[0063] Comparative Example 2
[0064] Compared with Example 1, the main difference is that konjac glucomannan is replaced by modified konjac glucomannan in step (2), and the specific scheme is as follows:
[0065] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during the electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0066] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and modified konjac gum in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of the modified konjac gum is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of the modified konjac gum; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1); during the electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac gum used in this step is 30% of the weight of the polylactic acid used in step (1);
[0067] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1), and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0068] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seed, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 4:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the water extract of the mixture of dark red rose and grape seed is 2% of the total weight of modified konjac gum and chitosan; electrostatic spraying is performed on the outer sides of both sides of step (3) using the electrostatic spray solution obtained in this step; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when electrostatic spraying is performed on the outer sides of both sides of step (3) in this step, the weight of the sum of modified konjac gum and chitosan used on each side is 30% of the weight of the polylactic acid used in step (1); after spraying is completed, placing in a special container and evacuating the residual organic solvent in the obtained membrane material to obtain a composite nano-membrane.
[0069] Comparative Example 3
[0070] Compared with Example 1, the main difference is that the chitosan in step (4) is replaced by gelatin. The specific scheme is as follows:
[0071] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during the electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0072] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1); during electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 30% of the weight of the polylactic acid used in step (1);
[0073] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1), and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0074] (4) collecting the film obtained in step (3); dissolving the water extract of the mixture of dark red rose and grape seed, modified konjac gum and gelatin in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and gelatin is 4:1, the weight fraction of the sum of modified konjac gum and gelatin is 1%, and the weight of the water extract of the mixture of dark red rose and grape seed is 2% of the total weight of modified konjac gum and gelatin; electrostatically spraying the outer sides of both sides with the electrostatic spray solution obtained in this step; during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when electrostatically spraying the outer sides of both sides of step (3) in this step, the weight of the sum of modified konjac gum and gelatin used on each side is 30% of the weight of the polylactic acid used in step (1); after spraying is completed, placing in a special container and evacuating the residual organic solvent in the obtained membrane material to obtain a composite nano-membrane.
[0075] Comparative Example 4
[0076] Compared with Example 1, the difference is that in this comparative example, a composite membrane alternately stacked by polylactic acid electrospinning membrane and modified konjac gum electrospinning membrane is prepared, and the specific scheme is as follows:
[0077] (1) Preparing a polylactic acid electrospun membrane: dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0078] (2) Preparation of modified konjac gum-chitosan electrospinning membrane: Spinning was performed on the basis of the obtained polylactic acid electrospinning membrane to cover the polylactic acid electrospinning membrane, specifically: modified konjac gum and chitosan (weight ratio of 4:1) were dissolved in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1 to form a spinning solution, wherein the weight fraction of the solute in the solution was 10%; during electrospinning, the voltage was 12 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0079] (3) repeating the electrospinning operation of step (1) on the membrane obtained in step (2);
[0080] (4) Repeating the electrospinning operation of step (2) on the membrane obtained in step (3);
[0081] (5) repeating the electrospinning operation of step (1) on the membrane obtained in step (4);
[0082] Thus, an electrospinning composite membrane with a 5-layer structure was obtained, and the weight ratio of the total weight of konjac gum and chitosan to the weight of polylactic acid in different layers was 3:10.
[0083] Comparative Example 5
[0084] Compared with Example 1, the main difference is that the water extract of the mixture of dark red roses and grape seeds is replaced by the water extract of dark red roses. The specific scheme is as follows:
[0085] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during the electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0086] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1); during electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 30% of the weight of the polylactic acid used in step (1);
[0087] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1), and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0088] (4) collecting the film obtained in step (3); dissolving the black red rose water extract, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 4:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the black red rose water extract is 2% of the total weight of modified konjac gum and chitosan; electrostatic spraying is performed on the outer sides of both sides of step (3); during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when electrostatic spraying is performed on the outer sides of both sides of step (3), the weight of the sum of modified konjac gum and chitosan used on each side is 30% of the weight of the polylactic acid used in step (1); after spraying is completed, the residual organic solvent in the obtained membrane material is volatilized by vacuumizing in a special container to obtain a composite nano-membrane.
[0089] Comparative Example 6
[0090] Compared with Example 1, the main difference is that the water extract of the mixture of black red roses and grape seeds is replaced by the water extract of grape seeds. The specific scheme is as follows:
[0091] (1) dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a polylactic acid weight fraction of 6%, and electrospinning the polylactic acid solution to form an electrospun fiber membrane; during the electrospinning, the voltage was 15 kV, the temperature was 25° C., the receiving distance was 15 cm, and the propulsion speed was 35 μL / min;
[0092] (2) collecting the electrospinning membrane obtained in step (1); dissolving the water extract of Zanthoxylum bungeanum and konjac glucomannan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 5:4 as an electrostatic spray solution, wherein the weight fraction of konjac glucomannan is 1%, and the weight of the water extract of Zanthoxylum bungeanum is 2% of the weight of konjac glucomannan; electrostatically spraying the electrostatic spray solution obtained in this step on one side of the electrospinning membrane obtained in step (1); during electrostatic spraying, the voltage is 20 kV, the temperature is 25° C., the receiving distance is 15 cm, and the propulsion speed is 50 μL / min; the weight of the konjac glucomannan used in this step is 30% of the weight of the polylactic acid used in step (1);
[0093] (3) Based on the product obtained in step (2), electrospinning is performed on the side where electrostatic spraying is completed according to the method of step (1), and the weight ratio of the polylactic acid used in this step to the polylactic acid used in step (1) is 1:1;
[0094] (4) collecting the film obtained in step (3); dissolving the grape seed water extract, modified konjac gum and chitosan in a mixed solvent composed of ethanol and acetic acid in a volume ratio of 1:1, as an electrostatic spray solution, the weight ratio of modified konjac gum and chitosan is 4:1, the weight fraction of the sum of modified konjac gum and chitosan is 1%, and the weight of the grape seed water extract is 2% of the total weight of modified konjac gum and chitosan; electrostatic spraying is performed on the outer sides of both sides of step (3); during electrostatic spraying, the voltage is 20kV, the temperature is 25°C, the receiving distance is 15cm, and the propulsion speed is 50μL / min; when electrostatic spraying is performed on the outer sides of both sides of step (3) in this step, the weight of the sum of modified konjac gum and chitosan used on each side is 30% of the weight of the polylactic acid used in step (1); after spraying is completed, placing in a special container and evacuating the residual organic solvent in the obtained membrane material to obtain a composite nano-membrane.
[0095] Experimental Example 1
[0096] Mechanical properties tests were performed on Examples 1 to 3, Comparative Example 1, Comparative Example 3, and Comparative Example 4. The tests were performed under the following three conditions: (1) After the composite nanofilm was prepared, the test was performed at 25°C, which was recorded as "0 hours"; (2) The composite nanofilm was placed at 45°C and 95% humidity for 24 hours, which was recorded as "high temperature and high humidity"; (3) After the composite nanofilm was coated with edible peanut oil, the test was performed at 45°C and 95% humidity for 3 hours, which was recorded as "oil immersion".
[0097] Tensile strength test method: Take 3 sections of 3cm composite nanofilm and randomly select 5 points in each section to measure its thickness, calculate the average value, which is the thickness, and calculate the cross-sectional area; randomly take a section of composite nanofilm, fix one end, and fix the other end in an empty mineral water bottle with a clip, so that the whole device is vertical to the ground, and then slowly add water to the mineral water bottle until the thin strip breaks, weigh the mineral water, calculate the maximum load and calculate the tensile strength. The tensile strength calculation formula is: tensile strength = maximum load / cross-sectional area.
[0098] Elongation at break test method: Cut 2.00 cm from the composite nanofilm, fix it on a vernier caliper, stretch it appropriately until it is about to break, and use the vernier caliper to calculate the length after stretching. Elongation at break = (length after stretching - length before stretching) / length before stretching.
[0099] The experimental results are shown in Table 1.
[0100] Table 1
[0101]
[0102] As shown in Examples 1 to 3 and Comparative Example 1 in Table 1, in step (4), after konjac gum is used to replace modified konjac gum, both tensile strength and elongation at break are significantly decreased under high temperature and high humidity or oil immersion conditions. At the same time, as shown in Examples 1 to 3 and Comparative Example 3 in Table 1, in step (4), chitosan is replaced by gelatin, and a similar situation also occurs.
[0103] In addition, as shown in Comparative Example 4, when the composite membrane is prepared by alternately stacking the polylactic acid electrospinning membrane and the modified konjac gum electrospinning membrane, the mechanical strength and the retention of mechanical strength are significantly worse than those of the composite nanomembrane obtained by the present invention, whether at 0°C or under high temperature and high humidity or oil immersion.
[0104] It can be seen that using polylactic acid as the inner layer material of the composite nano-membrane and using modified konjac gum and chitosan to form the outer electrostatic spray layer of the composite nano-membrane of the present invention is crucial for maintaining the mechanical strength.
[0105] Experimental Example 2
[0106] The antibacterial properties of Examples 1 to 3, Comparative Example 2, Comparative Example 5 and Comparative Example 6 were tested.
[0107] E. coli was cultured to the late logarithmic growth phase, the culture solution was centrifuged, the bacterial precipitate was washed with PBS three times, and then the bacterial cells were resuspended with PBS to adjust the bacterial concentration to 1×10 4 cfu / mL (calculated by plate count method) as the working solution. Take a composite nanofilm with a length and width of 1 cm, place it in the working solution, treat it at 25°C and 150rpm for 4 hours, then measure the bacterial concentration by plate count method, and calculate the inhibition rate according to the bacterial concentration before and after treatment.
[0108] The experimental results are shown in Table 2.
[0109] Table 2
[0110]
[0111] As shown in Example 1-3 and Comparative Example 2, in step (2), after konjac glucomannan is replaced by modified konjac glucomannan, the antibacterial property of the obtained composite nano film appears to be significantly reduced. The reason may be that the modified konjac glucomannan is relatively poor for the release of Zanthoxylum chinense aqueous extract relative to konjac glucomannan, so that the Zanthoxylum chinense aqueous extract and the water extract of the composite film outer antibacterial substance black red rose and grape seed mixture fail to form a good synergy. Meanwhile, as shown in Example 1-3 and Comparative Example 5 and Comparative Example 6, black red rose and grape seed water extract have synergy in antibacterial aspect, and after removing one of the water extracts, the antibacterial property of the composite nano film will appear to be significantly reduced.
[0112] Experimental Example 3
[0113] The composite nanofilm obtained in Example 1 was used to test the effect of packaging peaches. Peaches of uniform maturity, uniform size and weight of 180-200g were taken, and the peaches were completely wrapped and packaged with the film obtained in Example 1 as the experimental group (10 peaches); unpackaged peaches were used as the control group (10 peaches). The experimental group and the control group were stored at 4°C for 30 days, and the respiration intensity, enzyme activity, sugar-acid ratio, hardness, malondialdehyde and other indicators were examined. The respiration intensity of peaches in the experimental group was significantly lower than that of the control group. The respiration peak of the control group was on the 14th day (reaching 69.21 mL·(kg·h) -1 ), while the experimental group delayed the peak of respiratory rate to the 26th day (45.15 mL·(kg·h) -1 ); After 30 days, the polyphenol oxidase activity of the experimental group was 180U·g -1 , which was significantly lower than the polyphenol oxidase activity in the control group (330 U·g -1 ); After 30 days, the sugar-acid ratio of the experimental group was 35.2, significantly higher than that of the control group (22.3); After 30 days, the firmness of peaches in the experimental group decreased by 15%, while that in the control group decreased by 46%; After 30 days, the malondialdehyde content in the experimental group was 0.12 μmol˙kg -1 The malondialdehyde content in the control group was 0.58 μmol˙kg -1 It can be seen that the composite nanofilm obtained in Example 1 has a good preservation effect on peaches. Experiments show that peaches packaged with composite nanofilms still have good commercial value when stored at +4°C for 30 days. This storage method is significantly longer than the traditional 5-day cold storage period.
Claims
1. A method for preparing a high temperature, high humidity and oil resistant food preservative composite nanofilm, characterized in that: The high temperature, high humidity and oil resistant food preservation composite nano film is a multilayer structure, comprising a polylactic acid fiber film layer, a konjac gum antibacterial layer, and a modified konjac gum chitosan composite antibacterial layer; the preparation method comprises the following steps: (1) electrospinning a polylactic acid solution to form an electrospun fiber membrane as a first polylactic acid fiber membrane layer; (2) electrostatically spraying a konjac glucomannan solution containing an antibacterial substance A on one side of the electrospun membrane obtained in step (1) to form a konjac glucomannan antibacterial layer; (3) Based on the product obtained in step (2), electrospinning is performed using a polylactic acid solution on the side where the electrostatic spraying is completed to form a second polylactic acid fiber film layer; (4) electrostatically spraying the outer side of the obtained product of step (3) with a composite solution of modified konjac gum and chitosan containing an antibiotic B to form a composite antibacterial layer of modified konjac gum and chitosan; The modified konjac gum is obtained by acid hydrolyzing with citric acid, precipitating with ethanol, and freeze-drying the precipitate. In the composite solution of modified konjac gum and chitosan, the weight ratio of modified konjac gum to chitosan is 3 to 5:1; The antibacterial substance A is an aqueous extract of Zanthoxylum bungeanum leaves; the antibacterial substance B is an aqueous extract of a mixture of dark red roses and grape seeds, and the weight ratio of dark red roses to grape seeds is 2:1; When electrostatic spinning is performed in step (1) and step (3), the weight ratio of the polylactic acid used is 0.8-1.2:0.8-1.2; when electrostatic spraying is performed in step (2), the weight of the konjac glucomannan used is 0.2-0.4 times the weight of the polylactic acid used in step (1); when electrostatic spraying is performed in step (4), the total weight of the modified konjac glucomannan and chitosan used is 0.2-0.4 times the weight of the polylactic acid used in step (1).
2. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: The modified konjac gum is prepared by the following method: adding konjac gum to a citric acid aqueous solution so that the weight fraction of konjac gum is 10%, and the weight molar ratio of konjac gum to citric acid is 10g:1.6mmol; after stirring evenly, reacting at 80°C for 2 hours; then adding 2 times the volume of 95% ethanol aqueous solution, stirring evenly, standing to produce precipitation, and vacuum freeze-drying the precipitation to obtain the modified konjac gum.
3. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: The solvent in the polylactic acid solution is dichloromethane, and the weight fraction of polylactic acid in the polylactic acid solution is 6%.
4. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: The solvent of the konjac glucomannan solution in step (2) is a mixed solvent of ethanol and acetic acid mixed in a volume ratio of 5:4, and the weight fraction of konjac glucomannan in the konjac glucomannan solution is 1%.
5. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: In step (4), the solvent in the modified konjac gum and chitosan composite solution is a mixed solvent of ethanol and acetic acid mixed in a volume ratio of 1:1, the weight fraction of the sum of the modified konjac gum and chitosan is 1%, and the weight ratio of the modified konjac gum and chitosan is 4:
1.
6. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: When electrostatic spinning is performed in step (1) and step (3), the weight ratio of the polylactic acid used is 1:1; when electrostatic spraying is performed in step (2), the weight of the konjac glucomannan used is 0.3 times the weight of the polylactic acid used in step (1); when electrostatic spraying is performed in step (4), the weight of the konjac glucomannan used on each side is 0.3 times the weight of the polylactic acid used in step (1).
7. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 6, characterized in that: When electrospinning is performed in step (1) and step (3), the voltage is 15 kV, the temperature is 25°C, the receiving distance is 15 cm, and the propulsion speed is 35 μL / min; when electrostatic spraying is performed in step (2) and step (4), the voltage is 20 kV, the temperature is 25°C, the receiving distance is 15 cm, and the propulsion speed is 50 μL / min.
8. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: The preparation method of the water extract of Zanthoxylum bungeanum leaves is as follows: taking Zanthoxylum bungeanum leaves and chopping them, adding 10 times the weight of water, boiling and extracting for 2 hours, taking the filtrate to obtain a primary filtrate; adding 10 times the weight of water to the filter residue, boiling and extracting for 2 hours, taking the filtrate to obtain a secondary filtrate, combining the primary filtrate and the secondary filtrate to obtain a combined filtrate; and performing rotary evaporation drying on the combined filtrate to obtain the obtained product. The preparation method of the water extract of the mixture of dark red rose and grape seed is as follows: taking dark red rose according to the weight ratio and chopping them, mixing them with grape seeds, adding 15 times the weight of water, boiling and extracting for 2 hours, and taking the filtrate to obtain a primary filtrate; adding 15 times the weight of water to the filter residue, boiling and extracting for 2 hours, taking the filtrate to obtain a secondary filtrate, combining the primary filtrate and the secondary filtrate to obtain a combined filtrate; and performing rotary evaporation drying on the combined filtrate to obtain the obtained product.
9. The method for preparing a high temperature, high humidity and oil resistant food preservative composite nano film according to claim 1, characterized in that: The weight of the antibacterial substance A is 2% of the weight of the konjac gum; the weight of the antibacterial substance B is 2% of the total weight of the modified konjac gum and chitosan.
10. A high temperature, high humidity and oil resistant food preservation composite nano film, characterized in that: The food preservative composite nanofilm is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
A food packaging film that can be heated at high temperatures and its manufacturing process
CN115490965B
Method for preparing modified konjac glucomannan / biodegradation polyester polyblend fibers through electrostatic spinning
CN102926027A
Method for preparing high-toughness konjac glucomannan preservative film
CN105801890A
Fresh-keeping agent and fresh-keeping method for grosvenor momordica fruits
CN107897357A
Skin mucosa disinfection spray and preparation method thereof
CN115770269A